Ordination and the Boundaries of Biblical Theology - Gonzalez, Eliezer (Revista Hermenêutica (descontinuada), 2014)
Ordenação e os Limites da Teologia Bíblica Abstract There have been few serious attempts to develop theologies of ordination. This essay considers whether ordination lies within or outside the boundaries of Biblical theology. It analyses the topic of ordination from the perspective of Biblical theology. This essay demonstrates that it is not possible to argue for our contemporary concept of ordination from the Old Testament, that the Old Testament concepts of priesthood do not transfer to the New Testament (unless one adopts a sacramental theology), and that the term and the concept of ordination do not appear in the New Testament at all as we might recognize them in our contemporary setting. While arguments may be made for ordination from administrative necessity, tradition, and other theological systems, ordination must be understood as lying entirely outside the boundaries of Biblical theology. Keywords: Ordination; Biblical theology; priesthood; sacramental theology; New Testament. Resumo Houve poucas tentativas sérias para desenvolver teologias da ordenação. Este ensaio considera se a ordenação encontra-se dentro ou fora dos limites da teologia bíblica. Ele analisa o tema da ordenação a partir da perspectiva da teologia bíblica. Este ensaio demonstra que não é possível argumentar para o nosso conceito contemporâneo de ordenação do Antigo Testamento, que os conceitos do Antigo Testamento de sacerdócio não transferem para o Novo Testamento (a menos que se adota uma teologia sacramental), e que o termo ea conceito de ordenação não aparecem no Novo Testamento a todos como podemos reconhecê-los em nosso ambiente contemporâneo. Embora os argumentos podem ser feitas para a ordenação da necessidade administrativa, tradição, e outros sistemas teológicos, a ordenação deve ser entendida como inteiramente situada fora dos limites da teologia bíblica. Palavras-Chave: Ordination, Biblical theology, priesthood, sacramental theology, New Testament